Reduced Pelvic Floor Muscle Tone Predisposes to Persistence of Lower Urinary Tract Symptoms after Puerperium - Chandana Bhat; Mahjabeen Khan; Kirthinath Ballala; Asha Kamath; Deeksha Pandey (Scientifica)
Pregnant primiparous women at term were enrolled in the study. ICIQ-FLUTS questionnaire was used to find out prevalence of LUTS. MOS was used to assess pelvic floor muscle strength. Women were followed up after 8–10 weeks of delivery to find out remission or persistence of these symptoms. We found that increased frequency of micturition was the most common (82%) LUTS seen in primiparous women at term. More than half (51%) of these women who complained of LUTS had a poor pelvic floor muscle tone (MOS grade 3). Out of those who had symptoms during pregnancy 11% remained symptomatic even after puerperium. Interestingly 61% of those with persistence of symptoms demonstrated a very poor pelvic floor muscle tone at term (MOS grade 2), while the remaining 39% also had a tone of only MOS grade 3. Thus women with LUTS during pregnancy should be screened for their pelvic floor muscle tone with simple MOS system which will help to predict the persistence of these symptoms later on. Women with a low score (three or less) should be triaged for regular pelvic floor muscle exercises.